2014
DOI: 10.1007/s11999-014-3694-7
|View full text |Cite
|
Sign up to set email alerts
|

Do Inflammatory Markers Portend Heterotopic Ossification and Wound Failure in Combat Wounds?

Abstract: Background After a decade of war in Iraq and Afghanistan, we have observed an increase in combat-related injury survival and a paradoxical increase in injury severity, mainly because of the effects of blasts. These severe injuries have a devastating effect on each patient's immune system resulting in massive upregulation of the systemic inflammatory response. By examining inflammatory mediators, preliminary data suggest that it may be possible to correlate complications such as wound failure and heterotopic os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 25 publications
1
95
0
1
Order By: Relevance
“…In the neurogenic form, neurotransmitters such as glutamate, substance P, and catecholamines act to induce osteoblasts to form ectopic bone within a permissive local environment [5,18,27]. Therefore, the induction of progenitor cells with varying osteoinductive factors is common in both traumatic and neurogenic; however, the difference lies in the elevated levels of systemic and local inflammatory cytokines in the former and neurotransmitters in the latter [14]. That having been said, the expression and/or production of inflammatory mediators in this current study was not assessed; therefore, inferences regarding the role of local infection on HO development are based only on histopathological changes noted at study termination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the neurogenic form, neurotransmitters such as glutamate, substance P, and catecholamines act to induce osteoblasts to form ectopic bone within a permissive local environment [5,18,27]. Therefore, the induction of progenitor cells with varying osteoinductive factors is common in both traumatic and neurogenic; however, the difference lies in the elevated levels of systemic and local inflammatory cytokines in the former and neurotransmitters in the latter [14]. That having been said, the expression and/or production of inflammatory mediators in this current study was not assessed; therefore, inferences regarding the role of local infection on HO development are based only on histopathological changes noted at study termination.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cellular and early signaling mechanism(s) for combat injury-induced HO formation remain unclear. Recent findings suggest that the heightened and prolonged expression of inflammatory and other reparative mediators may be contribute to HO formation [11,14]. Moreover, the combat wound appears to provide a unique microenvironment conducive to osteogenesis that promotes the skewed differentiation of endogenous tissue-derived progenitor cells toward ectopic bone development within injured and healing soft tissue [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, wound fl uid markers have also been identifi ed, including increased expression of metalloproteinases (e. g. MMP-1, 2, 3, 7, 8, 9, 10, 11, 13), decreased expression of their inhibitors (e. g. TIMP-1) [61][62][63] , increased IL-1 and IL-6 [ 64 ] levels, as well as decreased levels of albumin and total protein [ 65 ] . Systemic biomarkers associated with a high risk of developing chronic wounds have also been reported, with chronic ulcer patients showing high serum levels of procalcitonin [ 66 ] as well as MMP3 and 2 [ 67 ] , and a reduced number of CD34+/CD45-dim circulating cells [ 68 ] and micro RNAs such as miRNA-200b and miRNA-191 [ 69 ] .…”
Section: Potential Biomarkers Of Impaired Wound Healingmentioning
confidence: 96%
“…At least 41% of those patients who develop HO require additional excision procedures. Moreover, delayed healing and wound dehiscence are major problems in severely injured patients recovering from survivable severe battlefield blast-related extremity injuries [12]. Studies from our group have established that acute wound failures and subsequent HO formation are related to multiple complex interrelated systemic and local inflammatory responses to traumatic injury [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…In this report, we use our model to address (1) the timing of early chondrogenesis, cartilage formation, and radiographic ectopic bone development; and (2) the early cartilage and bone-related gene and protein patterns in traumatized soft tissue subsequent to calcium deposition, tissue mineralization, and ectopic bone formation. It is important to confirm the timing and upregulation of bone-related genes and proteins in our model because some observational clinical studies with soft tissue injury (without fracture or amputation) have shown elevated levels of such genes in a minority of cases [6,9,12].…”
Section: Introductionmentioning
confidence: 99%